2005
DOI: 10.1094/pd-89-0872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wetness Duration and Grain Development Stages on Sorghum Grain Mold Infection

Abstract: Grain mold caused by a complex of fungi is an economically important disease of sorghum worldwide. Little is known about the epidemiology of sorghum grain mold, which is essential for its management. Studies were conducted to quantify the effects of wetness duration on grain mold development under controlled conditions at ICRISAT. Six major sorghum grain mold fungi determined from previous field experiments,Curvularia lunata, Cladosporium oxysporum, Bipolaris australiensis, Fusarium moniliforme, F. pallidorose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…The findings are in line with other studies done in South Africa (Chilaka, De Kock, Phoku, Mwanza, & Augustina, ; Phoku et al., ; Shabangu, ) and elsewhere (Egbuta et al., ; Mulunda et al, ; Mohale, Medina, Rodríguez, Sulyok, & Magan, ; Pacin et al., ; Saleemi et al., ) on maize. According to Navi et al., they are the major fungal genera commonly encountered in maize‐producing regions (Navi, Bandyopadhyay, Reddy, Thakur, & Yang, ). Aspergillus and Penicillium spp., however, usually co‐infect with Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are in line with other studies done in South Africa (Chilaka, De Kock, Phoku, Mwanza, & Augustina, ; Phoku et al., ; Shabangu, ) and elsewhere (Egbuta et al., ; Mulunda et al, ; Mohale, Medina, Rodríguez, Sulyok, & Magan, ; Pacin et al., ; Saleemi et al., ) on maize. According to Navi et al., they are the major fungal genera commonly encountered in maize‐producing regions (Navi, Bandyopadhyay, Reddy, Thakur, & Yang, ). Aspergillus and Penicillium spp., however, usually co‐infect with Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Direct application of fungal conidia to sorghum flowers and developing grain would appear to mimic natural infection (Navi et al 2005). Sorghum grain mold is likely caused by a species complex that may include Curvularia lunata, members of the F. moniliforme complex, Alternaria spp., Bipolaris spp., Cladosporium spp., or Phoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum grain mold is likely caused by a species complex that may include Curvularia lunata, members of the F. moniliforme complex, Alternaria spp., Bipolaris spp., Cladosporium spp., or Phoma spp. (Navi et al 2005). Tarekegn et al (2006) reported that moist and warm conditions post-flowering, including 3 to 19 days of precipitation, were highly favorable for grain mold infections.…”
Section: Discussionmentioning
confidence: 99%
“…Individual analysis of variance ( Influence of environmental variables, such as relative humidity and temperature, at grain maturity on infection by grain mold fungi and mold development has been well documented (Indira and Muthusubramanian, 2004;Navi et al, 2005). The significant mean squares due to year × A-line × R-line interactions suggested that the SCA effects are sensitive to seasonal changes over the years.…”
Section: Analysis Of Variancementioning
confidence: 99%